A politica de incentivos fiscais e o calculo do voto um estudo sobre o caso de Goiás - Silva, Alessandro Melo da (2014)
This study aims to investigate the relationship between public policy and electoral behavior. Specifically, the policy of tax incentives, which was implemented aggressively in the last twenty years. Our object is the case of the State of Goiás and from the volume of funds invested in the policy in question, we will assess the election results in the 246 municipalities in the State in four electoral cycles. To this end, we use quantitative methods to identify the correlation between the variables related to the policy of fiscal incentives and the election results. Three statistical models were built with the objective of clarifying how this governmental action can influence in electoral behavior. Finally, we present estimates of this impact. The results clearly indicate that the tax incentive policy and the election results in Goiás have high statistical relevance. ln the case studied, the electoral cycles in 2006, 2008 and 201 O, the policy benefits may have been a variable fairly representative. However, further studies should be developed, because the electoral behavior is a complex theme, where numerous variables and various theories are relevant and cannot be ignored.